Oxidative Stress and Opioids - Janka Vašková; Ladislav Kočan; Ladislav Vaško (Global Journal of Anesthesiology - Peertechz Publications, 2016)
In recent years, research has shown the involvement of free radicals in the development of the pain that accompanies many pathological conditions. In the treatment of acute and chronic pain, the most effective therapies are natural and synthetic opioid alkaloids. Their metabolism in itself may contribute to the formation of free radicals and thus affect body system load and the perception of pain. Long-term treatment with opioids is a tool of choice for the treatment of medium and severe pain. Opioids stimulate the effect of endogenous opioids, endorphins, by binding to multiple subtypes of opioid receptors (μ,κ,σ) in spinal, supraspinal and peripheral tissues. Morphine is a typical, natural opioid analgesic utilised in practice in the treatment of severe chronic pain. In addition, similar effects can be expected from semisynthetic opioids such as oxycodone and hydromorphone. However, during treatment with opioids some adverse effects can appear regardless of whether treatment is short-term or long-term. One potentially serious side effect is the induction of oxidative stress. The purpose of this present work is to determine the main sources of reactive oxygen and nitrogen in the development of infl ammatory and neuropathic pain, and the manner in which metabolism of morphine contributes to oxidative stress alone.